Flash Hacks - Bhangal, Sham (O'Reilly, 2011)
This collection offers expert Flash tips and tricks for optimization, creating interesting effects, ActionScript programming, sound and video effects, and much more--and you don't need to be an expert to use them (although you'll certainly look like one). Ranging from practical hacks to the fun and quirky, the book covers Flash MX, Flash MX 2004, and Flash MX Professional 2004. If you want more than your average Flash user, Flash Hacks is for you.